Banco postal e a inclusão financeira: uma análise espacial das atividades nos territórios de identidade da Bahia - BRENDLE, Vivian (2015)
The theme of this dissertation is financial inclusion, defined as a process of effective access and use by the population of financial services tailored to their needs and admitted as one of the ways to mitigate social inequality and to further economic growth, mainly, due to the benefits provided by the virtuous circle of appropriate financial inclusion. In Brazil, the main efforts to expand access to the National Financial System (SFN) focus on increasing and geographical equalization of banking service points and accessibility to services for low-income populations. The improvement of this process has close relationship with the spread of banking correspondents, which contribute substantially to the formation of an indicator of access to favorable SFN. In order to contribute to the debate on this issue, this paper discusses the performance of the correspondent bank Banco Postal, the role of financial inclusion agent in the state of Bahia identity territories. The study adopts the exploratory research and makes use of the descriptive method quantitative, based on data collected from secondary sources, and aims to spatially analyze the locational distribution of postal banks in the period 2009 to 2014 to evaluate the performance of the institution in the indentations territory from the establishment of financial inclusion index (IIF) applied to the Postal Bank. To this end, it makes use of the IIF calculation method adopted by the Central Bank of Brazil, maintaining the dimensions of analysis variables and their respective weights, in a specific focus to the activities of the Postal Bank. The results of the analyzed dimensions show that the spatial distribution of the Postal Bank premises in Bahia is against the policy of democratization of access to financial services to regions with lower economic dynamism. Whereas for the reproduction of mensuration methodology IIF volume of the observed financial variables are parameterized by the Gross Domestic Product of the municipalities, the absolute amounts calculated for the Postal Bank were greatly reduced in comparing with the overall national values, with classification low level of financial inclusion in 96% of identity territories. Therefore, the result obtained can not be used as a single reference to assess the degree of financial inclusion provided by the institution in the State, for which the analysis of this indicator was performed comparatively between identity territories. Finally, it is surmised from the study, the Postal Bank has proved as versatile instrument for achieving the expansion of banking service channels and has provided the real possibility of use of financial services to large sections of the Bahian population.